Pengaruh Pengetahuan Produk dan Prinsip-prinsip Syariah Terhadap Minat Memilih Bank Syariah - Saadah, Alamatus; Wisyananto, Arief (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2018)
This research tries to describe how employees respond to Islamic banking. This researchis quantitative which is the data has been used in this research is form of numbers. The sample inthis research were employees of the Teratai Putih Global 3 & 4 Vocational High School of Bekasi,amounting to 74 respondents were using saturated samples and collected data were processed usingSPSS version 24 analysis tool. The variables used in this research were product knowledge and shariaprinciples. As for the dependent variable is the interest in selecting Islamic banks. this research wasconducted by distributing questionnaires to respondents. The results of the research show that theresults of the tests F(?) indicate that the simultaneous test results have a significant positive effectwhich is the interest of employees is co-jointly influenced by product knowledge and sharia principles.And the persial test results of product knowledge variables and sharia principles have a significantpositive effect on employee interest.